Characterization of Air Void in Porous Asphalt Mixture Using Image Techniques and Permeability Test - Zhongping Tang; Fanglin Huang (Advances in Materials Science and Engineering)
In this study, air void contents and distributions of porous asphalt mixtures along the vertical and horizontal directions were quantitatively measured on planar images. Air void contents were determined using some image techniques; while the permeability was measured by the falling head test. Two aggregate gradations (G1 and G2) and three blow numbers (30, 40, and 50) were chosen to explore the effects of gradation and compaction effort on the porosity and permeability. Results showed that porosities and permeabilities are symmetrically distributed along the middle of the specimens; the porosities and permeabilities got the minimum values around the middle zone. A finer gradation or a significant compaction effort generally led to a lower porosity and permeability coefficient. In the horizontal direction, the air void content showed an increasing trend from the outside layer to the inner layer, indicating the nonuniformity of porosity distribution.